Biosynthesis of poly (3-hydroxybutyrate) (PHB) by cupriavidus necator H16 from jatropha oil as carbon source - Abeed Fatima, Mohidin Batcha (2014)
The increasing non-biodegradable plastic waste materials have created critical need in finding a better replacement to the currently available conventional plastic. Researches have shown great interest in the production of polyhydroxyalkanoate (PHA) biopolymer from bacterial fermentation. Although successful attempts have been made in producing these short to medium-chain length biopolymers, there are still problems in terms of yield and cost effectiveness that needs to be resolved. Poly(3-hydroxybutyrate) (PHB), a homopolymer of PHA is one particular example of bioplastic that are naturally produced by bacteria like Cupriavidus necator sp. By using plant oils such as jatropha oil as an alternative, a higher yield of PHB can be obtained and thus reducing the overall production cost of the biopolymers. In this study, Cupriavidus necator H16 was used to synthesize PHB by using jatropha oil as its sole carbon source. Different variables mainly jatropha oil and urea concentrations, and agitation speed were investigated to determine the optimum condition for microbial fermentation in batch culture. Based on the results, the highest cell dry weight and PHB concentration of 20.1 g/L and 15.5 g/L respectively was obtained when 20 g/L of jatropha oil was used along with 1 g/L of urea at 200 rpm of agitation speed. Ethanol was used as external stress factor and the addition of 1.5% (v/v) ethanol at 38 h had a positive effect with a high PHB yield of 0.987 g PHB/g jatropha oil. The kinetic studies for cell growth rate and PHB production were conducted and the data were fitted with Logistic and Leudeking Piret models. The rate constants were evaluated and the theoretical values were in accordance with the experimental data obtained. Optimization through Response Surface Methodology (RSM) at the condition of 0.9 g/L urea, 23.6 g/L jatropha oil and 251 rpm agitation speed resulted in 5% increase in PHB concentration to 17.92 g/L compared to the previously obtained PHB concentration of 17.05 g/L. The present work has succeeded in obtaining a high yield of PHB from an inexpensive raw material.